Quality Control Analysis on 100ML Bottle Products with Fault Tree Analysis Method Approach and Failur Mode and Effect Analysis - Wahyu Purnomo, Denny; Hermansyah , Muhammad (Journal Knowledge Industrial Engineering (JKIE), 2024)
This study analyzes quality control implementation for 100ml bottle production at PT. X using Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) methods. Data collected from February 15-29, 2021, revealed a 1% defect rate (7,110 bottles) from total production (788,700 bottles). Pareto analysis identified three dominant defects: Thick-Thin Walls (30%), Oil Stains (28%), and Fraying (13%), accounting for 71% of total defects. FTA root cause analysis traced these defects to human factors (operator errors), machine issues (uneven cavity temperature, misaligned components), and material problems (plastic mixing inconsistencies). FMEA assessment prioritized corrective actions based on Risk Priority Numbers (RPN), highlighting critical failures: uneven cavity diameter (RPN=432), oil-contaminated blue cores (RPN=384), and faulty thermo-couples (RPN=280). Proposed improvements include scheduled cavity maintenance, compressor overhauls for clean air supply, and thermo-couples calibration during product changeovers. The integrated FTA-FMEA approach demonstrates effectiveness in pinpointing systemic quality issues in blow molding processes, providing actionable insights to reduce defects by 40-50%. This research contributes to operational excellence in plastic manufacturing by combining defect visualization (Pareto) with causal-depth analysis (FTA) and risk quantification (FMEA).